Assessing the extent and determinants of adoption of improved cassava varieties in southwestern Nigeria - Awotide, B.; Abdoulaye, Tahirou; Alene, A.; Manyong, Victor M. (Academic Journals, 2014)
This paper investigates the determinants of adoption of improved cassava varieties in south-western Nigeria. The data come from a farm household survey of 841 households selected using a three-stage stratified random sampiling procedure. The data collection was conducted in 2011 by the International Institute of Tropical Agriculture (IITA), Ibadan, Nigeria. Empirical estimates of a Double-Hurdle model revealed that adoption increases with the age of the household head and is influenced by the gender of the household head, hired labour, cultivated land, and access to credit. The results further showed that the intensity of adoption is influenced by the hired labour and farm size; access to information about the improved cassava varieties is determined by the age, gender, and level of education of the household head, and by off-farm income.